2005
DOI: 10.1118/1.1992087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of edge effect due to phase contrast imaging for mammography

Abstract: It is well-known that the edge effect produced by phase contrast imaging results in the edge enhancement of x-ray images and thereby sharpens those images. It has recently been reported that phase contrast imaging using practical x-ray tubes with small focal spots has improved image sharpness as observed in the phase contrast imaging with x-ray from synchrotron radiation or micro-focus x-ray tubes. In this study, we conducted the phase contrast imaging of a plastic fiber and plant seeds using a customized mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Phase imaging with a digital X-ray detector in our study could not produce edge-enhanced images as was seen in phase imaging with use of an analogue X-ray detector [4,5]. The cause was that the edge-enhancement effect was reduced, because the resolution characteristic of a photostimulable phosphor plate of computed radiography was much inferior to that with an intensifying screen-film system.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Phase imaging with a digital X-ray detector in our study could not produce edge-enhanced images as was seen in phase imaging with use of an analogue X-ray detector [4,5]. The cause was that the edge-enhancement effect was reduced, because the resolution characteristic of a photostimulable phosphor plate of computed radiography was much inferior to that with an intensifying screen-film system.…”
Section: Discussionmentioning
confidence: 75%
“…Phase imaging is intended to provide edge enhancement (phase effect) of an imaged object, utilizing refracted X-rays which occur when X-rays pass through the object [3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…The theoretical consideration suggests that the phase-contrast effect would be more conspicuous in the images of fibroglandular tissue than calcification grains in the breast images. Matsuo et al (2005), in their empirical study of the total image quality evaluation including phase contrast, reported that phase contrast increases image signal as spatial frequency increases.…”
Section: Improvement Of Image Sharpness In Digital Full-field Pcmmentioning
confidence: 98%
“…A longer distance than typical clinical mammography values was utilized to target future applications, as this configuration has been used for preliminary studies in inline phase contrast x-ray imaging indicating the potential to reduce the dose in mammography without negatively affecting the detection capability [7,[35][36][37][38][39]. In addition, the air gap in this configuration provides a comparable amount of scatter rejection and resultant image quality improvement as the grid used in clinical systems [6,40,41]. The object was simulated by a BR12 phantom (Model 014A, CIRS, Norfolk, Virginia, USA) with a thickness of 5 cm.…”
Section: Inline X-ray Imaging System and Measurement Componentsmentioning
confidence: 99%